Peningkatan Aktivitas dan Hasil Belajar Menulis Teks Berita melalui Metode Pembelajaran Berbasis Masalah Siswa Kelas VIII C Semester Gasal SMP Negeri 1 Pabelan 2017/2018 - Fauziah W, Ratih (Faculty of Teacher Training and Education of Undaris, 2023)
This research aims to find out whether the learning activity of writing news texts for class VIII C students at SMP Negeri 1 Pabelan for the 2017/2018 academic year can be improved through problem-based learning methods and to find out what the learning outcomes for writing news texts for students at class VIII C at SMP Negeri 1 Pabelan are. The 2017/2018 academic year can be improved through problem-based learning methods.This research is classroom action research designed to be carried out in 2 cycles. Each cycle consists of planning, action, observation and reflection stages. The subjects of this research were students in class VIII C of SMP Negeri 1 Pabelan for the 2017/2018 academic year. This class was chosen because the results of learning to write news texts for this class were still below the expected minimum completeness criteria, namely 71.82.The research results showed that in cycle II the average score for students' learning activities to write news texts was 86.07 (high), while the average learning outcomes for students in writing news texts in cycle II reached a score of 85.51 (good). Classically, students have completed their studies because 93.75% of students have obtained a score of â‰¤ 76. Thus, the success indicator for this research has been achieved in cycle II so that this research can be declared successful in increasing students' activities and learning outcomes in writing news texts.Keywords: learning activities, learning outcomes, problem-based learning.